The Role of Liquid Smoke and Biochar Planting Media on Shallot Growth and Production (Allium ascalonicum L) - Seri Juni Yanti Harahap; Rasmita Adelina; Dini Puspita Yanty; Sutan Pulungan (International Journal of Natural Science Studies and Development (IJOSS), 2026)
Shallots (Allium ascalonicum L.) are a horticultural commodity with high sales value and a complete nutritional profile.. This study was conducted in Padang Lawas Regency from February to April 2025. The research method is an experimental study, using a factorial randomized block design. The first factor is Liquid Smoke consisting of 3 levels, namely: A0 = Without giving liquid smoke, A1 = Liquid smoke 70 ml / L, A2 = Liquid smoke 90 ml / L. Factor II is the provision of rice husk biochar with soil consisting of 3 levels, namely: B0 = Without giving rice husk biochar B1 = rice husk biochar 210 gr / polybag, B2 = rice husk biochar 300 gr / polybag, The parameters observed are Plant Height (cm), Number of Leaves (strands), Number of Bulbs Per Clump (bulbs), Wet Weight of Bulbs Per Clump (grams), Dry Weight of Bulbs Per Clump (grams) and Bulb Weight Loss (%). The data obtained were analyzed using statistical analysis of variance followed by the Least Significant Difference Test (LSD). The results of the study showed that the application of liquid smoke significantly affected growth (plant height) in the early vegetative phase (14 days after planting) and significantly affected shallot production (number of bulbs per clump). The use of liquid smoke at a treatment level of 70 ml/L and biochar at a treatment level of 300 g/polybag produced the best results for shallot cultivation.